2015
DOI: 10.1002/etc.2944
|View full text |Cite
|
Sign up to set email alerts
|

Dermal exposure of Eisenia andrei earthworms: Effects of heavy metals on metallothionein and phytochelatin synthase gene expressions in coelomocytes

Abstract: Parameters such as total number of coelomocytes, riboflavin content in coelomocytes, expression of genes implied in metal homeostasis, and detoxification mechanisms can be used as biomarkers to assess the impact of metals on annelids. Defense biomarkers (detoxification gene expressions and coelomocyte parameters) were investigated in the ecotoxicologically important species Eisenia andrei following in vivo exposure to 5 different metals (zinc, copper, nickel, lead, and cadmium) at known concentrations. Coelomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…It is indicated that E. fetida are sensitive to heavy metal exposure. Similar results were found in E. andrei exposed to Cd and Pb contaminated soils (Gitenay et al 2007;Li et al 2013;Homa et al 2015).…”
Section: Resultssupporting
confidence: 87%
“…It is indicated that E. fetida are sensitive to heavy metal exposure. Similar results were found in E. andrei exposed to Cd and Pb contaminated soils (Gitenay et al 2007;Li et al 2013;Homa et al 2015).…”
Section: Resultssupporting
confidence: 87%
“…Other studies on different earthworm species had some intriguing hints about possible regulation, but because they did not measure PC levels directly, the relationship to gene expression could not be determined. Brulle et al (2008) saw differences in PCS expression for Eisenia fetida at low but not high Cd concentrations, whereas Homa et al (2015) saw differences for Eisenia andrei for essential (Cu, Zn) but not non-essential metals (Cd, Pb).…”
Section: Resultsmentioning
confidence: 95%
“…A Cu- and Cd-induced induction of PCS, the enzyme responsible for the production of PC peptides, has been observed in E . andrei coelomocytes [40,41]. However, PCS gene expression did not change in L .…”
Section: Discussionmentioning
confidence: 99%